Preparation method of high-pressure-resistant and corrosion-resistant alumina ceramic nanofiltration membrane support

Through high-pressure hydrothermal method and microwave low-temperature sintering technology, combined with organic component additives, the fracture problem of ceramic nanofiltration membrane in high-pressure and high-corrosion environment is solved, the pressure and corrosion resistance of ceramic nanofiltration membrane is improved, and the pressure resistance and corrosion resistance of ceramic nanofiltration membrane is achieved. More stable ceramic nanofiltration membrane support preparation.

CN119215688APending Publication Date: 2024-12-31SUNTAR MEMBRANE TECHNOLOGY (XIAMEN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411246195.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing ceramic nanofiltration membranes are prone to fracture under high pressure and high corrosion environments, and the uneven addition of sintering additives leads to low strength and unstable performance of the ceramic membrane tube, and difficult to repair internal crack defects, affecting service life.

Method used

The nano-alumina is uniformly wrapped in the surface and internal cracks of the alumina ceramic particles by high-pressure hydrothermal method, and through microwave low-temperature sintering and vacuum mud training, combined with organic component additives, alumina ceramic nanofiltration is formed. membrane support.

Benefits of technology

It significantly improves the pressure resistance and corrosion resistance of ceramic nanofiltration membranes, reduces defect rate and unevenness, extends service life, and reduces the risk of membrane tube fracture in high-pressure environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215688A_ABST
    Figure CN119215688A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-pressure-resistant corrosion-resistant aluminum oxide ceramic nanofiltration membrane support, which comprises the following steps: firstly, uniformly wrapping the surfaces of aluminum oxide ceramic particles with nano particles by adopting a high-pressure hydrothermal method, and filling the nano particles into crack defects in the particles; then, a microwave low-temperature rapid one-time sintering method is adopted, a uniform and rapid heating mode is utilized, and the wave absorbing efficiency of the nanometer amorphous aluminum oxide particles is higher than that of the large-particle alpha-aluminum oxide, so that the nanometer aluminum oxide particles are stably and rapidly combined into the surface and internal cracks of the large-particle aluminum oxide ceramic powder. According to the method, the phenomena of desorption, agglomeration and segregation of nano-particles possibly occurring in the subsequent mixing, forming and sintering processes are effectively avoided, and the phenomena possibly cause defects and non-uniformity of the ceramic membrane support body. Meanwhile, compared with a traditional heating method, the microwave heating in the invention avoids the problems of uneven temperature distribution and abnormal agglomeration and growth of nanocrystals.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic membrane support preparation, and specifically relates to a method for preparing a high-pressure resistant and corrosion-resistant alumina ceramic nanofiltration membrane support. Background Art

[0002] Membrane technology and its related processes are a high-tech field that has rapidly emerged in the middle of the last century. They are currently highly valued worldwide and are regarded as key areas for scientific and technological innovation and national economic development. Compared with traditional polymer separation membranes, ceramic nanofiltration membranes have been widely used in industries such as petrochemicals, food processing, wastewater treatment, pharmaceutical technology and energy due to their high filtration accuracy, and have gradually occupied an important position in these fields, becoming a key technology in China's industrial transformation and upgrading.

[0003] However, ceramic nanofiltration membranes are usually used in some harsh environments, which have the following characteristics: First, high-pressure operation is necessary. In high-precision industrial filtration and separation processes, it is usually necessary to operate under high-pressure conditions to improve filtration efficiency and processing capacity. However, ceramic nanofiltration membranes on the market are prone to rupture under high operating pressures, which affects their service life. Secondly, chemical corrosion is a problem. When dealing with liquids containing strong acids, strong alkalis or organic solvents, ceramic nanofiltration membranes must have good chemical resistance. However, existing ceramic membrane supports may form internal cracks during the preparation process. These cracks are easy to expand and be chemically corroded during use, resulting in membrane tube rupture. Finally, mechanical vibration and impact are also common problems in practical applications. The ceramic nanofiltration membrane support is often affected by these external forces, which may cause the expansion of internal cracks, thereby causing the membrane support to rupture.

[0004] The ceramic nanofiltration membrane products currently on the market are prone to breakage and cracking in the above-mentioned harsh environments, which limits their widespread application in high-pressure and high-corrosion environments.

[0005] In the existing ceramic nanofiltration membrane support preparation process, it is necessary to add nano sintering aids to reduce the sintering temperature of the support. Usually, the sintering aid is added by direct mechanical mixing. However, since the nano sintering aid particles are easy to agglomerate, this may cause the sintering aid to be mixed unevenly with the large-particle ceramic powder of the support, and segregation is likely to occur during the sintering process, resulting in low strength or large fluctuations in the strength of the ceramic membrane tube, and unstable performance (such as Figure 1As shown). In addition, since the defect cracks of the ceramic aggregate particles are narrow and the surface is easy to absorb air and moisture after the cracks are broken, the agglomerated sintering aid cannot penetrate into the cracks or adhere to the crack surface. During the sintering process of the support body, the cracks inside these aggregate particles are not covered by the sintering aid, and the sintering temperature cannot reach the melting temperature, resulting in the inability to repair the cracks or sinter together, forming internal crack defects in the finished ceramic nanofiltration membrane support body. These crack defects are very susceptible to external force vibration during the transportation and high-pressure use of the membrane tube, causing crack expansion, resulting in the breakage and scrapping of the ceramic membrane tube. At the same time, the crack defects inside these particles are also susceptible to chemical corrosion during use, which seriously affects the safety and service life of the ceramic membrane tube. These problems ultimately lead to a series of problems such as many defects in the prepared support body, low pass rate, poor product stability, and easy breakage of the membrane tube under the high operating pressure of the ultrafiltration process, which seriously restricts the large-scale application and promotion of nanopore ceramic membranes. Summary of the invention

[0006] The purpose of the present invention is to overcome the defects of the prior art and provide a method for preparing a high-pressure resistant and corrosion-resistant alumina ceramic nanofiltration membrane support.

[0007] The technical solution of the present invention is as follows:

[0008] A method for preparing a high-pressure resistant and corrosion-resistant alumina ceramic nanofiltration membrane support, comprising the following steps:

[0009] (1) mixing a large-particle alumina ceramic powder having an average particle size of 10-45 μm with a nano-alumina dispersion having a concentration of 5-8 wt%, and reacting the mixture under high-pressure hydrothermal conditions of 8-16 MPa and 300-350° C. for 3-5 hours, wherein the average particle size of the nano-alumina in the nano-alumina dispersion is 5-20 nm;

[0010] (2) drying the material obtained in step (1), and then sintering it once at 650-850° C. for 25-35 min using a microwave heating device to obtain alumina powder;

[0011] (3) After sieving the alumina powder obtained in step (2), the alumina powder, corn starch with an average particle size of 0.8-1.2 μm and PVA with an average particle size of 0.8-1.2 μm are mixed evenly, and then RO water and glycerin are added and mixed evenly to form a ceramic mud material and aged;

[0012] (4) vacuum-kneading the material obtained in step (3) using a vacuum kneading machine, and then obtaining a wet blank by extrusion molding;

[0013] (5) The wet blank obtained in step (4) is shade-dried at room temperature, then dried, and then sintered at 1850-1980° C. for 3-5 hours to obtain the high-pressure resistant and corrosion-resistant alumina ceramic nanofiltration membrane support.

[0014] In a preferred embodiment of the present invention, in step (1), the purity of Al2O3 in the large-particle alumina ceramic powder is greater than 99.8%, and the purity of Al2O3 in the nano-alumina is greater than 99.9%.

[0015] In a preferred embodiment of the present invention, the drying temperature in step (2) is 120° C. and the drying time is 4 hours.

[0016] In a preferred embodiment of the present invention, the screening in step (3) is through a 120-500 mesh sieve.

[0017] In a preferred embodiment of the present invention, in step (3), the ratio of alumina powder, corn starch, PVA, RO water and glycerol is 76-80wt%: 3wt%: 2wt%: 13-16wt%: 2-3wt%.

[0018] Further preferably, in step (3), the average particle size of the corn starch is 1 μm, and the average particle size of the PVA is 1 μm.

[0019] In a preferred embodiment of the present invention, in step (4), the shade drying time is 18-24 hours; the drying temperature is 120° C. and the drying time is 2 hours.

[0020] In a preferred embodiment of the present invention, in the step (1), the purity of Al2O3 in the large-particle alumina ceramic powder is greater than 99.8%, and the purity of Al2O3 in the nano-alumina is greater than 99.9%; in the step (3), the ratio of alumina powder, corn starch, PVA, RO water and glycerol is 76-80wt%: 3wt%: 2wt%: 13-16wt%: 2-3wt%.

[0021] Further preferably, in step (3), the average particle size of the corn starch is 1 μm, and the average particle size of the PVA is 1 μm.

[0022] A ceramic nanofiltration membrane comprises a high-pressure resistant and corrosion-resistant alumina ceramic nanofiltration membrane support body prepared by the above preparation method.

[0023] The beneficial effects of the present invention are:

[0024] 1. The present invention first adopts a high-pressure hydrothermal method to uniformly wrap the nanoparticles on the surface of alumina ceramic particles and fill them into the crack defects inside the particles. Then, a microwave low-temperature rapid one-time sintering method is adopted, utilizing a uniform and rapid heating method, as well as the higher wave absorption efficiency of nano-amorphous alumina particles compared to large-particle α-alumina, to stably and rapidly combine the nano-alumina particles with the surface and internal cracks of large-particle alumina ceramic powders. This process effectively avoids the desorption, agglomeration and segregation of nanoparticles that may occur during subsequent mixing, molding and sintering processes, which may cause defects and non-uniformity in the ceramic membrane support. At the same time, compared with traditional heating methods, microwave heating avoids the problems of uneven temperature distribution and abnormal agglomeration and growth of nano-grains.

[0025] 2. The present invention only uses nano-alumina as a sintering aid, and all molding aids are organic components, which can be removed in the form of gas during high-temperature sintering. Therefore, the alumina content of the support body finally prepared can reach more than 99.8%, with low defect rate and uniform particle sintering connection.

[0026] 3. The high-pressure and corrosion-resistant alumina ceramic nanofiltration membrane support prepared by the present invention has a qualitative improvement in its compressive strength and corrosion resistance, which effectively solves a series of problems such as the many microscopic defects, low qualified rate, poor product stability of the existing conventional ceramic nanofiltration membrane support, and easy breakage of the membrane tube under the high operating pressure of the ultrafiltration process, thus providing a strong guarantee for the large-scale application and promotion of nanopore ceramic membranes. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a scanning electron microscope photograph of a ceramic nanofiltration membrane support body prepared by the existing ceramic nanofiltration membrane support body preparation process in the background technology of the present invention.

[0028] Figure 2 This is a scanning electron microscope photograph of the alumina powder prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further illustrated and described below through specific implementation modes in combination with the accompanying drawings.

[0030] Example 1

[0031] (1) mixing large-particle alumina ceramic powder (purity of Al2O3>99.8%, average particle size of 10 μm) with nano-alumina dispersion (concentration of 8 wt%, purity of Al2O3>99.9%, average particle size of 5 nm), and reacting under high pressure (16 MPa) hydrothermal (350°C) conditions for 4 h;

[0032] (2) The material obtained in step (1) was dried at 120° C. for 24 h, and then sintered at 650° C. for 30 min using a microwave heating device to obtain alumina powder (such as Figure 2 As shown, microwave heating avoids the problems of uneven temperature distribution and abnormal agglomeration and growth of nano-grains);

[0033] (3) After the alumina powder obtained in step (2) is passed through a 500-mesh sieve, the alumina powder, corn starch (average particle size 1 μm) and PVA (average particle size 1 μm) are mixed in a mixer for 4 hours, and then RO water (16 wt%) and glycerol (3 wt%) are added. After mixing for another 4 hours, ceramic mud is formed and aged for 48 hours, wherein the ratio of alumina powder, corn starch, PVA, RO water and glycerol is 76 wt%: 3 wt%: 2 wt%: 16 wt%: 3 wt%.

[0034] (4) The material obtained in step (3) is subjected to vacuum kneading by a vacuum kneading machine, and then a wet blank is obtained by extrusion molding.

[0035] (5) The wet blank obtained in step (4) is dried in the shade at room temperature for 20 hours, then slowly heated to 120° C. in an oven and dried for 2 hours, and then subjected to secondary high-temperature sintering in a high-temperature sintering electric kiln at 1850° C. for 3 hours to obtain the high-pressure resistant and corrosion-resistant alumina ceramic nanofiltration membrane support.

[0036] (6) coating one or more layers of filtration membrane on the high-pressure and corrosion-resistant alumina ceramic nanofiltration membrane support prepared in step (5) by a ceramic filtration membrane preparation process such as dipping or spraying to finally prepare a ceramic nanofiltration membrane.

[0037] According to the relevant test methods in HY / T 064-2002 "Test Methods for Tubular Ceramic Microporous Filter Membranes", the performance of the ceramic nanofiltration membrane is: the bursting pressure resistance reaches 28-30MPa, and the bursting pressure after strong acid corrosion only decreases by 2.3%, and the bursting pressure after strong alkali corrosion only decreases by 3.5%. In comparison, the bursting pressure resistance of the ceramic nanofiltration membrane based on the ceramic membrane support body made by simple mechanical mixing of the same raw materials is only 10-15MPa, and the bursting pressure after strong acid corrosion decreases by 16%, and the bursting pressure after strong alkali corrosion decreases by 24%.

[0038] Example 2

[0039] (1) mixing large-particle alumina ceramic powder (purity of Al2O3>99.8%, average particle size 45 μm) with nano-alumina dispersion (concentration of 6 wt%, purity of Al2O3>99.9%, average particle size 20 nm), and reacting under high pressure (8 MPa) hydrothermal (300°C) conditions for 4 h;

[0040] (2) drying the material obtained in step (1) at 120° C. for 24 h, and then sintering the material at 850° C. for 30 min using a microwave heating device to obtain alumina powder (the specific morphology is basically the same as that of Example 1);

[0041] (3) After passing the alumina powder obtained in step (2) through a 120-mesh sieve, the alumina powder, corn starch (average particle size 1 μm) and PVA (average particle size 1 μm) are mixed in a mixer for 4 hours, and then RO water (16 wt%) and glycerol (3 wt%) are added. After mixing for another 4 hours, ceramic mud is formed and aged for 48 hours, wherein the ratio of alumina powder, corn starch, PVA, RO water and glycerol is 80 wt%: 3 wt%: 2 wt%: 13 wt%: 2 wt%.

[0042] (4) The material obtained in step (3) is subjected to vacuum kneading by a vacuum kneading machine, and then a wet blank is obtained by extrusion molding.

[0043] (5) The wet blank obtained in step (4) is dried in the shade at room temperature for 20 hours, then slowly heated to 120° C. in an oven and dried for 2 hours, and then subjected to secondary high-temperature sintering in a high-temperature sintering electric kiln at 1980° C. for 5 hours to obtain the high-pressure resistant and corrosion-resistant alumina ceramic nanofiltration membrane support.

[0044] (6) coating one or more layers of filtration membrane on the high-pressure and corrosion-resistant alumina ceramic nanofiltration membrane support prepared in step (5) by a ceramic filtration membrane preparation process such as dipping or spraying to finally prepare a ceramic nanofiltration membrane.

[0045] According to the relevant test methods in HY / T 064-2002 "Test Methods for Tubular Ceramic Microporous Filter Membranes", the performance of the ceramic nanofiltration membrane is: the bursting pressure resistance reaches 23-26MPa, and the bursting pressure after strong acid corrosion only decreases by 3.5%, and the bursting pressure after strong alkali corrosion only decreases by 4.3%. In comparison, the bursting pressure resistance of the ceramic nanofiltration membrane based on the ceramic membrane support body made by simple mechanical mixing of the same raw materials is only 8-9MPa, and the bursting pressure after strong acid corrosion decreases by 18%, and the bursting pressure after strong alkali corrosion decreases by 29%.

[0046] Example 3

[0047] (1) mixing large-particle alumina ceramic powder (purity of Al2O3>99.8%, average particle size 30 μm) with nano-alumina dispersion (concentration of 5 wt%, purity of Al2O3>99.9%, average particle size 15 nm), and reacting under high pressure (13 MPa) hydrothermal (330°C) conditions for 4 h;

[0048] (2) drying the material obtained in step (1) at 120° C. for 24 h, and then sintering the material at 750° C. for 30 min using a microwave heating device to obtain alumina powder (the specific morphology is basically the same as that of Example 1);

[0049] (3) After passing the alumina powder obtained in step (2) through a 200-mesh sieve, the alumina powder, corn starch (average particle size 1 μm) and PVA (average particle size 1 μm) are mixed in a mixer for 4 hours, and then RO water (16 wt%) and glycerol (3 wt%) are added. After mixing for another 4 hours, ceramic mud is formed and aged for 48 hours, wherein the ratio of alumina powder, corn starch, PVA, RO water and glycerol is 78 wt%: 3 wt%: 2 wt%: 15 wt%: 2 wt%.

[0050] (4) The material obtained in step (3) is subjected to vacuum kneading by a vacuum kneading machine, and then a wet blank is obtained by extrusion molding.

[0051] (5) The wet blank obtained in step (4) is dried in the shade at room temperature for 20 hours, then slowly heated to 120° C. in an oven and dried for 2 hours, and then subjected to secondary high-temperature sintering in a high-temperature sintering electric kiln at 1950° C. for 4 hours to obtain the high-pressure resistant and corrosion-resistant alumina ceramic nanofiltration membrane support.

[0052] (6) coating one or more layers of filtration membrane on the high-pressure and corrosion-resistant alumina ceramic nanofiltration membrane support prepared in step (5) by a ceramic filtration membrane preparation process such as dipping or spraying to finally prepare a ceramic nanofiltration membrane.

[0053] According to the relevant test methods in HY / T 064-2002 "Test Methods for Tubular Ceramic Microporous Filter Membranes", the performance of the ceramic nanofiltration membrane is: the bursting pressure resistance reaches 25-28MPa, and the bursting pressure after strong acid corrosion only decreases by 3.2%, and the bursting pressure after strong alkali corrosion only decreases by 3.9%. In comparison, the bursting pressure resistance of the ceramic nanofiltration membrane based on the ceramic membrane support body made by simple mechanical mixing of the same raw materials is only 10-13MPa, and the bursting pressure after strong acid corrosion decreases by 15%, and the bursting pressure after strong alkali corrosion decreases by 26%.

[0054] According to the above embodiments, the bursting pressure of the support prepared by the present invention can reach 25-30MPa, and the bursting pressure after strong acid corrosion only decreases by 2-3%, and the bursting pressure after strong alkali corrosion only decreases by 3-5%. In contrast, the alumina ceramic nanofiltration membrane support prepared by the prior art method has a bursting pressure resistance of only 8-15MPa, and the bursting pressure after strong acid corrosion decreases by 10-30%, and the bursting pressure after strong alkali corrosion decreases by 20-40%.

[0055] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.

Claims

1. A method for preparing a high pressure resistant and corrosion resistant alumina ceramic nanofiltration membrane support, characterized in that: The steps include: (1) mixing a large-particle alumina ceramic powder having an average particle size of 10-45 μm with a nano-alumina dispersion having a concentration of 5-8 wt%, and reacting the mixture under high-pressure hydrothermal conditions of 8-16 MPa and 300-350° C. for 3-5 hours, wherein the average particle size of the nano-alumina in the nano-alumina dispersion is 5-20 nm; (2) drying the material obtained in step (1), and then sintering it once at 650-850° C. for 25-35 min using a microwave heating device to obtain alumina powder; (3) After sieving the alumina powder obtained in step (2), the alumina powder, corn starch with an average particle size of 0.8-1.2 μm and PVA with an average particle size of 0.8-1.2 μm are mixed evenly, and then RO water and glycerin are added and mixed evenly to form a ceramic mud material and aged; (4) vacuum-kneading the material obtained in step (3) using a vacuum kneading machine, and then obtaining a wet blank by extrusion molding; (5) The wet blank obtained in step (4) is shade-dried at room temperature, then dried, and then sintered at 1850-1980° C. for 3-5 hours to obtain the high-pressure resistant and corrosion-resistant alumina ceramic nanofiltration membrane support.

2. The preparation method according to claim 1, characterized in that: In the step (1), the purity of Al2O3 in the large-particle alumina ceramic powder is greater than 99.8%, and the purity of Al2O3 in the nano-alumina is greater than 99.9%.

3. The preparation method according to claim 1, characterized in that: The drying temperature in step (2) is 120° C. and the drying time is 4 hours.

4. The preparation method according to claim 1, characterized in that: The sieving in step (3) is through a 120-500 mesh sieve.

5. The preparation method according to claim 1, characterized in that: In the step (3), the ratio of alumina powder, corn starch, PVA, RO water and glycerol is 76-80wt%: 3wt%: 2wt%: 13-16wt%: 2-3wt%.

6. The preparation method according to claim 5, characterized in that: In the step (3), the average particle size of the corn starch is 1 μm, and the average particle size of the PVA is 1 μm.

7. The preparation method according to claim 1, characterized in that: In the step (4), the shade drying time is 18-24 hours; the drying temperature is 120° C. and the drying time is 2 hours.

8. The preparation method according to claim 1, characterized in that: In the step (1), the purity of Al2O3 in the large-particle alumina ceramic powder is greater than 99.8%, and the purity of Al2O3 in the nano-alumina is greater than 99.9%; in the step (3), the ratio of alumina powder, corn starch, PVA, RO water and glycerol is 76-80wt%: 3wt%: 2wt%: 13-16wt%: 2-3wt%.

9. The preparation method according to claim 8, characterized in that: In the step (3), the average particle size of the corn starch is 1 μm, and the average particle size of the PVA is 1 μm.

10. A ceramic nanofiltration membrane, characterized in that: The invention comprises a high-pressure resistant and corrosion-resistant alumina ceramic nanofiltration membrane support body prepared by the preparation method described in any one of claims 1 to 9.